2017
DOI: 10.1111/ppl.12545
|View full text |Cite
|
Sign up to set email alerts
|

Oilseed rape NAC56 transcription factor modulates reactive oxygen species accumulation and hypersensitive response‐like cell death

Abstract: The NAC (NAM, ATAF1/2, CUC2) transcription factor gene family is plant-specific and plays diverse roles in development and responses to abiotic stresses and pathogen challenge. Oilseed rape (Brassica napus) or canola is an important oil crop worldwide, however, the function of NAC genes in it remains largely elusive. In the present study, we identified and characterized the NAC56 gene isolated from oilseed rape. Expression of BnaNAC56 was induced by abscisic acid (ABA), jasmonic acid (JA), methyl viologen (MV)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 35 publications
0
14
0
Order By: Relevance
“…BnNAC19 and BnNAC82 have been shown to induce a hypersensitive response and cell death under stress due to ROS accumulation (Wang B. et al, 2015). Independent studies have reported similar observations in tobacco and B. napus protoplasts due to transient expression of BnNAC55, BnNAC56, BnNAC87, and BnNAC103 (Niu et al, 2014;Niu et al, 2016;Chen et al, 2017;Yan et al, 2017). Contrary to this transgenic rice overexpressing SNAC3 showed enhanced tolerance to high temperature, drought, and oxidative stress caused by methyl viologen (MV) due to lower accumulation of ROS (Fang et al, 2015).…”
Section: Nacs Tfsmentioning
confidence: 84%
“…BnNAC19 and BnNAC82 have been shown to induce a hypersensitive response and cell death under stress due to ROS accumulation (Wang B. et al, 2015). Independent studies have reported similar observations in tobacco and B. napus protoplasts due to transient expression of BnNAC55, BnNAC56, BnNAC87, and BnNAC103 (Niu et al, 2014;Niu et al, 2016;Chen et al, 2017;Yan et al, 2017). Contrary to this transgenic rice overexpressing SNAC3 showed enhanced tolerance to high temperature, drought, and oxidative stress caused by methyl viologen (MV) due to lower accumulation of ROS (Fang et al, 2015).…”
Section: Nacs Tfsmentioning
confidence: 84%
“…The transcription of NAC089 is itself promoted by two membrane bound TFs, bZIP28 and bZIP60, highlighting the multiple levels of regulation involved in initiating the PCD cascade ( Yang et al., 2014 ). In rapeseed, four NAC TFs (BnaNAC55, BnaNAC56, BnaNAC87, and BnaNAC103) have separately been shown to be involved in PCD following treatment with diverse abiotic stressors ( Niu et al., 2014 ; Niu et al., 2016 ; Chen et al., 2017 ; Yan et al., 2017 ). In all cases, expression of the respective TF resulted in the development of HR-like lesions, reactive oxygen species (ROS) accumulation, and DNA degradation, however, the molecular mechanisms by which these TFs induce cell death has not been examined.…”
Section: Nac Transcription Factorsmentioning
confidence: 99%
“…In the transcriptomic analysis, treatment contrast group (a), detailing plants that were treated with aphids in relation to untreated plants, DEGs encoding tansy orthologs of NAC56 transcription factor and a TMV resistance protein N were upregulated. The NAC56 transcription factor (TF) is known to play a role in plant responses to abiotic stress and challenge by pathogens [45]. Chen and colleagues demonstrated that in Brassica napus (oilseed rape), BnNAC56 was significantly induced by JA, SA, and ABA, indicating that it may play a central role in plant tolerance of biotic stresses.…”
Section: Gene Expression Identification Of Genes Differential Respomentioning
confidence: 99%